A espacialidade da Igreja Evangélica Assembleia de Deus em Cuiabá – MT - Carlos, Rosana Samara de Souza Santos (2021)
The structure of this work has the function of reflecting the specialty of the Assembly of God Evangelical churches of Cuiabá, from its Headquarters Church and all the branches within the city. The Great Temple was inaugurated in 1996, where large events, meetings, social actions, among others take place. Among the procedures adopted, bibliographic and documental surveys stand out. This work seeks to focus on the processes of spatiality and territoriality of the city, power relations and the consequent formation of a religious territory in Cuiabá, Mato Grosso. In this city, we observe the expressive presence of the Assemblies of God Churches, which has approximately 300 congregations, including a church for Haitians only. All are managed in a hierarchical manner, with the Headquarters Church and the other churches subordinated to it by sectors. Each sector has a sub-headquarter, which is responsible for managing social issues and festivities held in its area. Thus, it has a “symbolic” center in the city, which is a reference for Christians and adherents of the Assembly of God - Great Temple. Therefore, we analyze the territorial organization of the sacred and the conflicts around its territory in Cuiabá, MT, in order to demonstrate the influence of religiosities in the construction of cities and their conflicts for power and space. The religious man feels the need to live in an atmosphere permeated by the sacred, which is why they elaborate techniques for the construction of the sacred. From this perspective, constructions are shaped by the ideas of a society, whose forms of economic and social organization, distribution of resources and authority are part of its activities, beliefs and values.